PERANAN BKKBN DALAM PEMBANGUNAN KESEJAHTERAAN SOSIAL (Suatu Studi di Badan Keluarga Berencana, Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Minahasa Selatan) - KAWULUR, ANDRE; DENGO, SALMIN; ROMPAS, SONNY (Sam Ratulangi University, 2015)
ABSTRACTIn accordance with the duties and functions BKKBN or Regional FamilyPlanning Agency has a strategic role in the development of social welfare . The role willbe realized as expected if the Family Planning Agency may formulate and implementprograms that are directly related to efforts to repair / improvement of social welfare inparticular the families of the target group . In connection with this, this peneleitianendak answer the question